Statistical overview and empirical literature on foreign direct investment in developing countries - Édouard Mien (Fondation pour les études et recherches sur le développement international (FERDI), 2023)
This note aims to provide an overview of Foreign Direct Investment (FDI) in developing countries. First, we present the recent trends of global FDI flows, and identify the main hosting areas as well as the variables promoting FDI inflows. Then, we briefly describe the empirical literature on the economic impacts of FDI on recipient countries. Finally, we present some recent changes in public policies implemented in developing countries aiming at attracting FDI inflows.
Keywords: 330